2023
DOI: 10.1038/s41598-023-32115-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between nonalcoholic fatty liver disease and peripheral neuropathy in US population, a cross-sectional study

Abstract: Nonalcoholic fatty liver disease (NAFLD) has become an important risk of type 2 diabetes mellitus (T2DM). Peripheral neuropathy (PN) is regarded as one of the main microvascular complications of diabetes. But the association of NAFLD with PN is still unclear. We aimed to investigate the association between NAFLD and PN in US population by conducting a cross-sectional study. We enrolled 3029 participants aged 40–85 years from National Health and Nutrition Examination Survey (NHANES) 1999–2004. NAFLD was defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Within the complete cohort, 943 individuals (25.1%) were exempt from NAFLD, whereas 1 498 (39.8%) were diagnosed with NAFLD. In earlier studies involving 3 029 participants, it was determined that 1 250 individuals, constituting 41.27% of the sample, had been diagnosed with NAFLD (17). Consequently, our study's observed prevalence of NAFLD closely corresponds to the ndings of previous research, indicating a robust concordance between our results and the existing literature.…”
Section: Discussionsupporting
confidence: 90%
“…Within the complete cohort, 943 individuals (25.1%) were exempt from NAFLD, whereas 1 498 (39.8%) were diagnosed with NAFLD. In earlier studies involving 3 029 participants, it was determined that 1 250 individuals, constituting 41.27% of the sample, had been diagnosed with NAFLD (17). Consequently, our study's observed prevalence of NAFLD closely corresponds to the ndings of previous research, indicating a robust concordance between our results and the existing literature.…”
Section: Discussionsupporting
confidence: 90%
“…Gu et al reported a significant association between NAFLD and peripheral neuropathy in the general population aged 40-64 years, both in nondiabetic and diabetic individuals [ 12 ]. They utilized the US FLI score for NAFLD detection and conducted a monofilament assessment of neuropathy, a subjective test for peripheral neuropathy assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, small fiber neuropathy presents with impaired pain, temperature perception, and autonomic functions [ 11 ]. Recently, Gu et al 2023 reported a significant association and concluded that the small nerve fibers get affected in NAFLD [ 12 ]. They used the US fatty liver index (FLI) score for NAFLD detection and the monofilament test for the assessment of peripheral neuropathy.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension was diagnosed if participants had elevated blood pressure on at least three occasions, were taking anti-hypertensive medication, or had received a medical diagnosis of hypertension. Hyperlipidemia could be diagnosed if participants had elevated total cholesterol, triglycerides, low-density lipoprotein, or low levels of high-density lipoprotein ( Gu et al, 2023 ), see the detailed information in Supplementary Table 2.…”
Section: Methodsmentioning
confidence: 99%